Flexible Temporary Shield in Soft and Sensitive Clay: 3D FE Modelling of Experimental Field Test. (25th February 2021) - Alam, Miah; Chaallal, Omar; Galy, Bertrand
Abstract : A finite-element (FE) numerical study using PLAXIS-3D software was carried out to reproduce and validate a full-scale experimental in situ test and to investigate the earth pressure on a flexible temporary trench box shield in soft and sensitive clay soil. The excavation trench model was 6 m (20 ft) deep and was considered as nonlinear and anisotropic clay. A 45 kPa (0.94 ksf) surface overload on top of the soil near the trench box was also simulated to produce a maximum load case on the flexible wall of the shield. Both Mohr-Coulomb (MC) and hardening soil (HS) constitutive soil models were considered for FE analysis. Different values of the modulus reduction factor (MRF) and the coefficient of earth pressure at rest (K 0 ) were considered to validate the model. For a specific shear strength profile, FE analysis with a linear elastoplastic soil model showed relatively small differences in soil pressure with the field test results along the depth of the trench. Results were also compared with the predictions of well-established analytical formulae.